Integrating constructivist approaches in e-learning to enhance mathematical self-study - Lee, Ya Ling (2005)
E-learning models are currently practised widely all over the world due to the rapid growth of distance and global education. Furthermore, e-learning provides high quality educational offerings (Seufert 2002) and allows a convenient and flexible learning environment without restriction of learning space, distance and time (Albrechtsen et al. 2001). Hence, distance education is widely accepted by most of the nontraditional learners (Williams et al. 2002; Leonard & Guha 2001). Open University Malaysia (OUM) is one of the distance education universities in Asia that involves in hybrid concepts for learning. With advance media and communication technologies, OUM is capable of conducting courses using a combination of self-study process (provided with printed learning material), fortnightly face to face tutorials (five tutorials, two hours each per semester) and online communication (between studentsstudents and students-tutors).